Spatial evolution model of port group hinterland from the perspective of intermodal transport. Issue 3 (3rd April 2023) - Huang, Guangyu; Feng, Xuejun; Chen, Mili; Jiang, Liupeng; Wang, Haipeng; Wang, Suyang
ABSTRACT: The rapid development of the intermodal system has led to the intensification of the hinterland competition within the port group, and the spatial pattern of the hinterland has become discontinuous. Based on geographic information system technology, a spatial interaction model, in which the intermodal cost distance is computed by integrating the raster analysis method and network method, is developed to facilitate the examination of the spatial evolution process of the port group intermodal hinterland. Considering the example of the Gulf of Guinea port group in West Africa, the spatial evolution process of its five ports is simulated in three scenarios. The results indicate that intermodal transport drives the hinterland's discontinuous development, and the direction and layout of the intermodal corridors significantly impact the hinterland competition of the port group. In most cases, the intermodal corridors can help realize connected ports to enhance the hinterland's competitive advantage within the port group. However, adjacent ports may also benefit from this aspect under certain conditions, which implies the importance of port cooperation in planning collection and distribution corridors. The model and findings can theoretically support the decision-making of port investors and operators.